QUOTATION AND USE OF THE RIGHT TO QUOTE IN DOCTORAL THESES. QUOTATION SYSTEMS USED IN SCIENTIFIC WORKS IN THE FIELD OF LAW - Alexandru STAN (Challenges of the Knowledge Society, 2022)
The quotation represents both a right and an obligation of any author, even more so of the aspirants for the title of doctor. In order to be able to write a scientific paper, a detailed study of national and international law, quotation rules and the use of a quotation system approved by the scientific community is required. It is obvious that a study on a topic that has been debated before should start with the analysis of previous specialized papers, and the quotation of the opinions, theories and conclusions of our predecessors appears as a mandatory element, as long as the new scientific paper considers similar coordinates. At the same time, the quotation must be made in accordance with good conduct in scientific research, so as not to prejudice in any way the moral rights of the original author, which is why the sources must be indicated, the reproductions must be short and not alter in any way the quoted text. The author of a paper must use one of the quotation systems recognized by the international community, and in the particular case of scientific works in the field of law the most used is the Chicago Manual of Style, the advantages of using this system being, among others: simplicity of quotation with which the work can be completed, the possibility of quickly verifying any similarities or the ease footnotes can be used with.